Más cara la lavada que la camisa: Un análisis de la legitimidad para obrar extraordinaria en los procesos de tutela colectiva con pretensiones indemnizatorias - Crestani Queirolo, Chiara Lucia (Pontificia Universidad Católica del Perú, 2023)
The purpose of this research is to analyse, from an economic perspective, whether it is efficient to grant extraordinary legitimacy to act in proceedings on behalf of a collective group when claims for damages are sought. In this sense, the hypothesis formulated is that not all collective protection proceedings should have the same regulation in relation to the representative person of the community. In collective rights proceedings or in proceedings where homogeneous it may be more efficient for a member of the class, who is one of the affected parties, to represent the group. After the investigation, it is concluded that the regulation of collective protection is a challenging task and precisely because of its difficulty, the legal system should allow the affected group to determine, from an effectiveness point of view, who should represent them.
Keywords: Derecho procesal civil--Perú; Intereses difusos; Tutela jurisdiccional--Regulación; https://purl.org/pe-repo/ocde/ford#5.05.01